Systematic Review on Innovation and Economic Growth in Developing Countries between 2019-2023 - Proaño Ramón, Hugo Alexander (2024)
Innovation is fundamental for sustainable development; thus, this article aims to analyze and synthesize the literature on the relationship between innovation and economic growth in developing countries. To achieve this, a bibliographic review was conducted in databases such as Scopus, Web of Science, and repositories like Redalyc and SciELO, selecting 11 articles from a total of 200 using the PRISMA method. The inclusion criteria focused on studies about innovation in local contexts and publications from 2019 to 2023, excluding research unrelated to developing countries. The results highlight that investment in research and development (R&D), strengthening technological capabilities, and intersectoral collaboration are essential for promoting innovation. The conclusions emphasize the need for policies that support technical education and the creation of innovation networks, critical elements for sustainable economic growth in these countries.